An improved mobility state detection mechanism for femtocells in LTE networks - Maiwada, U.D. (Institute of Electrical and Electronics Engineers Inc., 2022)
The usage of femtocells, or micro macrocell base stations, increases energy efficiency which enhance quality of service for both indoor and outdoor customers. Femtocells were used in 4GP's (Fourth Generation Project) LTE (Long Term Evolution) and advanced LTE like the 5G/6G networks to improve indoor coverage and capacity of the network. However, the random deployment of femtocells, as well as the large number and size variables, make controlling mobility even more difficult because mobile users increase day by day. This research investigates energy efficiency for femtocell mobility state detection algorithms to increase the QoS in LTE and advanced LTE networks (5G/6G networks). Several systems for detecting movement are currently in place. However, when it comes to cell type information and parameter scaling difficulties, they are found wanting as they help to improve the QoS. Overall handover performance suffers because of this gap that present techniques fail to address. As a remedy, this study presents an Improved Mobility State Detection Mechanism (IMSDM). As a result of the findings, IMSDM appears to be a viable way to improve energy efficiency for handover performance deterioration to increase the QoS and information about the cell type problems. It did not minimize the probability on Radio Link Failure (RLF), but it did give a decent trade-off among RLF likelihood since it is reduced and the quantity of Ping-Pong handovers. Â© 2022 IEEE.